Developmental origins of endometriosis: a Swedish cohort study. Issue 4 (19th January 2019) - Gao, Menghan; Allebeck, Peter; Mishra, Gita D; Koupil, Ilona
Abstract : Background: Endometriosis is a chronic condition affecting women of reproductive age and is associated with multiple health burdens. Yet, findings regarding its 'developmental origins' are inconsistent. We aimed to investigate the associations of birth characteristics with endometriosis. We also explored potential mediation by adult social and reproductive factors. Methods: This cohort study consisted of 3406 women born in Uppsala, Sweden, between 1933 and 1972. We used data from archived birth records and endometriosis diagnoses at ages 15–50 recorded in the national patient registers. Socioeconomic and reproductive characteristics were obtained from routine registers. HRs were estimated from Cox regression. Results: During the follow-up, 111 women have been diagnosed with endometriosis, and most cases are external endometriosis (ie, outside the uterus, n=91). Lower standardised birth weight for gestational age was associated with increased rate of endometriosis (HR 1.35 per standard deviation decrease; 95% CI 1.08 to 1.67). This increased rate was also detected among women with fewer number of live births (HR 2.38; 95% CI 1.40 to 4.07 for one child vs ≥2 children; HR 6.09; 95% CI 3.88 to 9.57 for no child vs ≥2 children) and diagnosed infertility problem (HR 2.00; 95% CI 1.10 to 3.61) prior to endometriosis diagnosis. All the observed associations were stronger for external endometriosis. However, no evidence was found that number of births was the mediator of the inverse association between standardised birth weight and endometriosis. Conclusion: This study supports the developmental origins theory and suggests that exposure to growth restriction during the fetal period is associated with increased risk of endometriosis during reproductive years.